Interleukin-12 Enhances Antifungal Activity of Human Mononuclear Phagocytes against Aspergillus fumigatus: Implications for a Gamma Interferon-Independent Pathway - Roilides, Emmanuel (American Society for Microbiology, 1999)
The potential of recombinant human interleukin-12 (IL-12) to enhance the capacity of human monocytes (MNC) to elicit an oxidative burst and damage hyphae of Aspergillus fumigatus was investigated. Incubation of peripheral blood mononuclear cells (PBMC) from healthy adults with 10 to 100 ng of IL-12/ml at 37°C for 2 to 3 days enhanced the production of superoxide anion (O(2)(−)) in response to phorbol myristate acetate (PMA) (P = 0.04) and unopsonized A. fumigatus hyphae (P = 0.03) and further enhanced hyphal damage (P = 0.009). Anti-gamma interferon (anti-IFN-γ) blocked secretion of IFN-γ by IL-12-treated PBMC but did not inhibit IL-12-induced O(2)(−) production by these cells in response to PMA. In addition, IL-12-treated elutriated MNC secreted no IFN-γ or tumor necrosis factor alpha but exhibited enhanced O(2)(−) production compared to controls (P = 0.013). These findings demonstrate that IL-12 augments oxidative antifungal activities of MNC via an IFN-γ-independent route, suggesting a novel pathway of IL-12 action in antifungal defense.